Race-based educational, occupational and industry segregation and wages gaps in Trinidad and Tobago - Caroline Schimanski; Cristian Chagalj; Inder S. Ruprah (Inter-American Development Bank (IDB), 2018)
In the light of Trinidad and Tobago's colonial history, its labour market is characterized by two about equal sized majority racial groups that had during colonialism been highly segregated in terms of education, occupation, industry and sector of work and facing a large institutionalized pay difference. This raises the question whether segregation and historical wage gaps still exist and are affected by the government in power. Therefore, this study provides evidence of race-based educational, occupational and industry segregation and wage gaps in Trinidad and Tobago's private and public sector and its development, using labour market survey data from 1999 to 2015. Despite its history, aggregate racial educational and occupational segregation are with 7% in terms of the Karmel-Maclachlan index low and lower than respective gender-based segregation over the same period and have remained constant over the sample period. Most of the race-based occupational segregation is a result of preceding educational segregation. In aggregate terms the racial wage gap has in the initial years been negligibly small but rising over time and shifting from initially favouring ATTs to favouring ITTs. There is however large heterogeneity both in terms of segregation and wage gaps across education levels, occupations, industries and sectors. Racial wage gaps appear larger in the public sector, in particular for women. Also there is indicative evidence that the racial share of public sector workers and public sector wage gaps is affected by the party in power. Using quantile regression and decomposition techniques, this study furthermore provides evidence of large heterogeneity in returns to education and a shift in the direction of the average wage gap from favouring ATTs to favouring ITTs along the entire wage distribution.
Keywords: J15; J24; J31; J71; N16; 330; Caribbean; educational segregation; occupational segregation; wage gaps; race